A new virus discovered by immunocapture of double‐stranded RNA, a rapid method for virus enrichment in metagenomic studies. (4th April 2016) - Blouin, Arnaud G.; Ross, Howard A.; Hobson‐Peters, Jody; O'Brien, Caitlin A.; Warren, Ben; MacDiarmid, Robin
Abstract: Next‐generation sequencing technologies enable the rapid identification of viral infection of diseased organisms. However, despite a consistent decrease in sequencing costs, it is difficult to justify their use in large‐scale surveys without a virus sequence enrichment technique. As the majority of plant viruses have an RNA genome, a common approach is to extract the double‐stranded RNA (dsRNA) replicative form, to enrich the replicating virus genetic material over the host background. The traditional dsRNA extraction is time‐consuming and labour‐intensive. We present an alternative method to enrich dsRNA from plant extracts using anti‐dsRNA monoclonal antibodies in a pull‐down assay. The extracted dsRNA can be amplified by reverse transcriptase–polymerase chain reaction and sequenced by next‐generation sequencing. In our study, we have selected three distinct plant hosts: Māori potato ( Solanum tuberosum ), rengarenga ( Arthropodium cirratum ) and broadleaved dock ( Rumex obtusifolius ) representing a cultivated crop, a New Zealand‐native ornamental plant and a weed, respectively. Of the sequence data obtained, 31–74% of the reads were of viral origin, and we identified five viruses including Potato virus Y and Potato virus S in potato; Turnip mosaic virus in rengarenga (a new host record); and in the dock sample Cherry leaf roll virus and a novel virus belonging to the genus Macluravirus . We believe that this new assay represents a significant opportunity to upscale virus ecology studies from environmental, primary industry and/or medical samples.